Compact Circularly Spiral Planar Inverted-F Antenna for Medical Implant Application - Argya Harish; Achmad Munir (IAES Indonesia Section, 2014)
A combination technique to reduce the physicaldimension of device to be more compact is proposed in this paperto design an antenna for medical implant application. Two designtechniques, i.e. planar inverted-F and geometry modification, arecombined and implemented to construct a compact circularlyspiral planar inverted-F antenna (PIFA) to operate aroundfrequency of 920MHz. The antenna is deployed on an FR4Epoxy dielectric substrate with the thickness of 0.8mm. Before thehardware realization, the parameters of antenna including reflectioncoefficient, voltage standing wave ratio (VSWR), gain, andradiation pattern as well as its physical dimension are investigatednumerically to obtain the optimum performance design. Fromexperimental characterization, it shows that the realized antennain circular shape which has the diameter of 18mm resonatesat frequency of 911MHz with measured bandwidth and gain of20MHz and -29.82dBi, respectively.